Analysis of Students’ Errors in Solving Function Derivative Application Problems Based on Watson’s Error Criteria - Ela Susanti; Neneng Aminah; Dede Endang Mascita (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2025)
In adressing problems related to the application of derivatives of function, many students demonstrate inadequate mastery of derivative concepts. It leads to various mistakes in solving derivative application problems. This study aims to analyze student’s errors in solving derivative application problems based on Watson's error criteria. This research employs a qualitative method with descriptive approach. The data analyzed in this study were derived from the formative test on the topic of derivatives of functions administered to students in Class XII MIPA 3. Three students were selected as subjects based on the types of errors they have made. The instruments were developed based on tests results and interviews, which were then analyzed using the Watson's error criteria. The interviews employed semi-structured protocol to gain deeper insights about the errors made by the students in solving derivative application problems. The interview results were presented in the form of transcripts. Results showed that the types of student’s errors are include incorrect procedural steps, missing data, incomplete conclusions, hierarchy skill issues, and response-level conflicts. These findings are expected to serve as a reference for future research and to provide insights for mathematics teachers of the potential errors made by students, particularly in solving derivative application problems.